Síndrome de stauffer en pacientes con adenocarcinoma renal - Anguisaca Velez, Karen Estefania (Machala : Universidad Técnica de Machala, 2019)
Introduction: Renal cell carcinoma (RCC) is the most frequent malignant renal tumor within the group of renal tumors, assuming that 90% of these tumors are the neoplasms, and the third most frequent urological tumor; Within its paraneoplastic manifestations, we have Stauffer syndrome, which consists of a non-metastatic liver dysfunction, which is present in various malignant diseases, including renal adenocarcinoma. Objective: Establish the therapy in a patient with Stauffer syndrome in renal adenocarcinoma. Methodology: It was carried out through the search of information in bibliographic reviews of several scientific articles in journals indexed and reviewed by academic peers, obtained in the database: Pubmed, Scielo, Elsevier, Google Academic, etc., published during the last 5 years, related to Stauffer Syndrome in patients with Renal Adenocarcinoma. Conclusion: Nephrectomy as a treatment has given excellent results with survival of > 5 years. In addition, there are no studies where another type of drug is used to cause treatment efficacy.
Introducción: El carcinoma de células renales (CCR) es el tumor renal maligno más frecuente dentro del grupo de los tumores renales, suponiendo que el 90 % es de estas neoplasias, y el tercer tumor urológico más frecuente; dentro de sus manifestaciones paraneoplasica tenemos el síndrome de Stauffer que consiste en una disfunción hepática no metastásica, que está presente en diversas enfermedades malignas dentro de las que se incluye el adenocarcinoma renal. Objetivo: Establecer la terapéutica en paciente con síndrome de Stauffer en adenocarcinoma renal. Metodología: Se realizó mediante la búsqueda de información en revisiones bibliográficas de varios artículos científicos en revistas indexadas y revisadas por pares académicos, obtenidas en la base de datos: Pubmed, Scielo, Elsevier, Google Académica, etc., publicados durante los últimos 5 años, relacionados con el Síndrome de Stauffer en pacientes con Adenocarcinoma Renal. Conclusión: La nefrectomía como tratamiento ha dado excelente resultado con sobrevida de > 5 años. Además, no existen estudios en donde se utilice otro tipo de fármaco para provocar eficacia de tratamiento.
Keywords: CARCINOMA DE CELULAS RENALES; TUMOR RENAL; SINDROME DE STAUFFER; ADENOCARCINOMA RENAL